Implementasi Pelatihan Pewarnaan Batik Shibori dalam Meningkatkan Ekonomi Kreatif Masyarakat Desa Pranan - Fitri Yaningsih, Yunita; Intan Junita; Dwiana Oktavia; Alif Mazida Salsabila (Jurnal Bina Desa, 2024)
The implementation of Shibori batik dyeing training aims to enhance the creative economy of Pranan Village. This community service activity focuses on empowering local communities, especially women, to develop their skills in the traditional art of batik. Through a series of workshops and demonstrations, participants learn various Shibori techniques and natural dyeing methods. The training is expected to increase the quality and diversity of batik products, thus expanding market opportunities and generating additional income for the community. The results of this activity show a significant improvement in the participants' skills and a growing interest in developing batik-based businesses. This project contributes to preserving cultural heritage while promoting sustainable economic growth.